Pengaruh Learning Management System Berbasis Moodle terhadap Kemampuan Literasi Membaca Siswa Kelas V Sekolah Dasar - Aulia, Yosi; Nafiah; Syamsyul Ghufron; Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low reading literacy skills of fifth-grade elementary school students, influenced by limited reading interest, inadequate literacy activities, and the dominance of conventional teaching methods. The study aimed to determine students' reading literacy skills before and after the implementation of a Moodle-based Learning Management System (LMS) and to examine its effect on the reading literacy skills of fifth-grade elementary school students. This research employed a quantitative approach using a Pre-Experimental One-Group Pretest-Posttest Design. The sample consisted of 26 students of Class V-A of SDI Iskandar Said Surabaya, selected through purposive sampling. Data were collected using a reading literacy test developed from the AKM and PISA indicators and analyzed using descriptive statistics and the Paired Sample t-Test. The results revealed that the implementation of the Moodle-based LMS had a significant positive effect on students' reading literacy. The mean score increased from 52.65 in the pretest (categorized as